Social Inequality in Vietnam and the Challenges to Reform - Taylor, Philip, 1962- (Book collections on Project MUSE., 2004)
Social inequalities have grown during Vietnam's transition to a market-based economy, even as average incomes have increased and the number of people living in poverty has lessened. Do widening social rifts -- between rich and poor, urban and rural communities and along regional, gender and ethnic lines -- have the potential to undermine Vietnam's liberal reforms and its integration with its region? How has the socialist state responded to these challenges? Based on research and analysis of recent conditions, Social Inequality in Vietnam and the Challenges to Reform offers detailed description.